Računalniško podprta analiza slike mikro- in makroobjektov - Levanič, Tom (Zbornik gozdarstva in lesarstva, 1999)
Presented herewith are the possibilities of image analysis of micro- and macroobjects in wood technology and forestry. Described hardware and software needed to established an operational image analysis system. There is also described how to convert analogue pictures into a digital form and how to enhance image quality of the image. Image analysis is a five step process: (1)capturing the image, (2) enhancing the quality, (3) thresholding, (4) calibration of the system and (5) measuring. Measuring could be done on the original image for density studies or on thresholded images for different kinds of object analysis. Finally, some theoretical and practical examples arepresented. Key words
Keywords: computer science; dendrologija; les; morfologija; računalniška grafika; računalništvo; slike; zgradba